Literature Review: Potensi Tanaman Serai (Cymbopogon Citratus) sebagai Antidiabetes - Saldi, Andini Putri; Atifah, Yusni (MASALIQ, 2024)
The World Health Organization (WHO) explains that more than 220 million people worldwide have diabetes mellitus. Diabetes mellitus is a chronic metabolic disorder caused by not producing enough insulin. Treatment of DM is costly and often has side effects that can be detrimental to the body. Therefore, traditional medicine using herbal plants has begun to be developed at this time. A plant that has the potential as an antidiabetic is lemongrass. This study aims to determine the potential of lemongrass plants as antidiabetics. The method used in writing this article is Literature Review Article (LRA). The database source uses Publis or Perrish. The data used are journal articles published from 2013 to 2023. The results of the literature review that has been carried out know that lemongrass plants have potential as antidiabetics. The antidiabetic ability of lemongrass is due to the presence of secondary metabolite compounds such as flavonoids, tannins, steroids, alkaloids, and triterpenoids contained in lemongrass plants that have the ability to reduce blood glucose levels.